A model for generative artificial intelligence in customer decision-making process using social interaction - Hodjat (Hojatollah) Hamidi (Telematics and Informatics Reports)
In light of the rapid and unpredictable developments in artificial intelligence (AI), there is a growing need for innovative marketing strategies that can expand market reach and effectively promote services. AI and social interaction have emerged as powerful tools in modern marketing, particularly through the use of social media platforms to enhance product awareness and drive customer engagement. This study investigates the factors influencing customer decision-making in relation to participation in Generative Artificial Intelligence (GAI)-based marketing. Drawing on prior research in the field, the study introduces a conceptual model incorporating key variables such as age, Internet usage, information quality, and information credibility. To examine the proposed model, a questionnaire was administered to students from universities in Tehran. The collected data were analyzed using appropriate statistical methods. The findings reveal that customer satisfaction and customer inertia significantly influence customer decisions to engage in smart marketing practices. Among the evaluated variables, information quality was identified as the most impactful factor, while Internet usage had the least influence. These results provide practical insights for marketers and researchers aiming to leverage GAI in customer-oriented strategies.